The impact of acute radiodermatitis on quality of life in breast cancer patients receiving conventionally fractionated versus hypofractionated breast irradiation - Nagwa E Abd Elazim; Maha S El-Nagga; Rania H Mohamed; Sara M Awad (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2020)
Background: Although prior studies have examined the effect of radiation-induced skin toxicity on patients' Quality of Life (QOL), little is known about the effect of radiotherapy on skin-related QOL with different radiotherapy schedules. Objective: To assess the impact of radiodermatitis on the quality of life in patients undergoing conventionally fractionated versus hypofractionated radiation therapy for breast cancer. Methods: We conducted a prospective study including breast cancer patients undergoing radiotherapy. Patients were evaluated at the initial visit, weekly during radiotherapy and 2weeks after the end of treatment. Radiodermatitis was graded weekly using Common Terminology Criteria of Adverse Events (CTCAE) version 4.0. Patient reported symptoms of pain or itching were also assessed on Visual Analogue Scale (VAS). The Skindex-16 QOL instrument was administered at 1 week of initiation and 2weeks after the completion of radiotherapy.  Results: Thirty patients completed the study and received either Conventional Radiotherapy (CRT) (15 patients) or Hypofractionated Radiotherapy (HRT) (15 patients). A total of 16 patients (53.3%) developed grade 1 radiodermatitis and 3(20%) developed grade 2 throughout the study. All patients receiving HRT had their radiodermatitis cleared at the end of treatment, while 9 patients (60%) had persistent radiodermatitis after CRT. Lower pain scores were reported with HRT than with CRT. Patients in the HRT group reported better QOL scores for symptom and emotion domains at 2week-follow-up compared to baseline while no significant change was found in any of domain scores after CRT. Conclusion: Our results demonstrated the advantage of HRT in improving RD and patient reported discomfort in breast cancer patients compared to CRT. A beneficial effect for HRT was also noted in the improvement of patients' QOL particularly in the symptom and emotional domains. Therefore, it is important to include patient QOL measures when evaluating patients undergoing radiotherapy so that the treatment approach can be modified to improve QOL.